Stochastically perturbed allelopathic phytoplankton model - Syed Abbas; Malay Banerjee (Electronic Journal of Differential Equations, 2010)
In this article we have considered a stochastic delay differential equation model for two species competitive phytoplankton system with allelopathic stimulation. We have extended the deterministic model system to a stochastic delay differential equation model system by incorporating multiplicative white noise terms in the growth equations for both species. We have studied the mean square stability of coexisting state using a suitable Lyapunov functional. Numerical simulation results are provided to validate the analytical findings.